Kolaborasi Model Pembelajaran SFE dengan Talking Stick untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Moh Iqbal Fathoni; Sholahudin Al 'Ayubi; Muhlisatul Mahmudah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This study aims to determine the improvements of students’ activities and learning outcomes in studying the digestive linier equation system of two variables (SPLDV) with learning model collaboration of Student Facilitator And Explaining (SFE) with Talking Stick. The type of research is a classroom action research (CAR). The results revealed that the percentage of students’ learning ativities in the first cycle was 91,6% and the second cycle was 94,65%. Furthermore, the results of tests yielded that the students’ scores in the first cycle obtained average value 80% and the average value in the second cycle was 95%. It is proved that the students’ activities and learning outcomes can be improved with the implementation of Learning model collaboration of Student Facilitator and Explaining (SFE) with Talking Stick. Keywords: Student facilitator and explaining, talking stick, learning activity, learning outcomes.